(untitled) (Global Journal of Management and Business Research, 2022)
The financial analysis of a company implemented through ratios alone can lead to making completely erroneous judgements about the dynamic development of the company s income and expenditure For this reason cash flows and the statement that summarises them represent essential elements of the study of the company s financial performance Various international bodies have addressed this issue since in most countries the cash flow statement now identifies one of the elements that make up the financial reporting for the year on par with the balance sheet and profit and loss Here we will take a closer look at the central bodies that have addressed this issue and illustrate what has been said about cash flow and the cash flow statement by the American FASB the IASB the Italian Civil Code and the Italian Accounting Standards Board As you will see all of these bodies propose structures or examples of items requiring the highlighting and re-grouping of needs and sources into three aggregates operating activities investing activities and financing activities Subsequently we will point out that information limitations characterise these statements Therefore we will propose drafting a report structured according to the logic of an integrated information system i e a system in which all the documents forming part of financial reporting and management control are consistent at a substantial and formal level and therefore at the level of the terminology used